Inflation and welfare in long-run equilibrium with firm dynamics - Alexandre Janiak; Paulo Santos Monteiro (Institute for the Study of Labor (IZA), 2009)
We analyze the welfare cost of inflation in a model with cash-in-advance constraints and an endogenous distribution of establishments' productivities. Inflation distorts aggregate productivity through firm entry dynamics. The model is calibrated to the United States economy and the long-run equilibrium properties are compared at low and high inflation. We find that, when the period over which the cash-in-advance constraint is binding is one quarter, an annual inflation rate of 10 percent leads to a decrease in the steady-state average productivity of roughly 0.5 percent compared to the optimum's steady-state. This decrease in productivity is not innocuous: it leads to a doubling of the welfare cost of inflation.
Keywords: E40; E50; L16; O40; 330; Firm dynamics; productivity; inflation; welfare; Inflation; Unternehmensentwicklung; Produktivität; Markteintritt; Wohlfahrtseffekt; USA